Digitization of religious artifacts with a structured light scanner - Alejandro Graciano; Lidia Ortega; Rafael J. Segura; Francisco R. Feito (Virtual Archaeology Review)
The digitization process for religious artifacts is subject to inherent difficulties often ignored in theoretical models or pipelines. In this paper we aim to describe these problems, which are present in practical environments such as temples and churches, using white light scanners instead of other common devices or technologies such as laser scanners and photogrammetry. Our case study is based on the digitization of two religious statues belonging to a Catholic brotherhood located in a village of the Province of Jaén (Spain), one of them presenting especially several limitations. After performing the scanning process with a portable hand-held scanner, the images captured were processed until the final models were acquired. On the basis of the results obtained, we discuss the problems arising after using well-known procedures for the reconstruction of 3D models, their causes and some possible solutions to achieving a correct digitization. It should be noted that it is not the aim of this study to establish procedures for the digitization of religious artifacts, but rather to transmit the inherent constraints of these types of scenes.